Comparative transcriptomic analyses of two sugarcane Saccharum L. cultivars differing in drought tolerance - Li, Haibi; Gui, Yiyun; Zhu, Kai; Wei, Jinju; Zhang, Ronghua; Yang, Rongzhong; Tang, Liqiu; Zhou, Hui; Liu, Xihui (Frontiers in Plant Science, 2023)
Sugarcane (Saccharum spp.) is an important cash crop,, and drought is one of thean important factors limiting its yield. In order tTo study the drought resistance mechanism of sugarcane, the transcriptomes of two sugarcane varieties with different levels of drought resistance levels were compared under different water shortage levelsconditions. The results showed that the transcriptomes of the two varieties were significantly different. DThe differentially expressed genes (DEGs)were enriched in starch and sucrose metabolism, linoleic acid metabolism, Gglycolysis/Ggluconeogenesis, and Gglyoxylate and dicarboxylate metabolic pathways. Unique trend genes of thein variety with strong drought resistance (F172) were significantly enriched in Pphotosynthesis, Mmitogen-activated protein kinases (MAPK) signaling pathway, biosynthesis of various plant secondary metabolites, and cyanoamino acid metabolism pathways. The wWeighted correlation network analysis (WGCNA) indicated that the blue4 and plum1 modules were correlated with drought conditions, whereas the tan and salmon4 modules were correlated with variety. The unique trend genes expressed in F172 and mapped to thein blue4 module were enriched in photosynthesis, urine metabolismpurine metabolism, starch and sucrose metabolism, beta-alanine metabolism, photosynthesis-antenna proteins, and plant hormone signal transduction pathways. The expression of genes involved in the phyotosynthesisantenna protein pathway and phyotosynthesis pathways decreased in response to water deficit , indicating thatand reducing photosynthesis might be a meansway for sugarcane to responding to drought stress. The results of this study provide insights into drought resistance mechanisms in plants, and the related genes and metabolic pathways identified may be helpful infor sugarcane breeding in the future.